Term Limits and Collaboration Across the Aisle: An Analysis of Bipartisan Cosponsorship in Term Limited and Non-Term Limited State Legislatures. (June 2016) - Swift, Clint S.; VanderMolen, Kathryn A.
As members of democratic institutions, state legislators must frequently collaborate with each other to achieve their varied goals. Given the increased attention to questions of polarization and gridlock, scholars should be particularly interested in understanding legislator decisions to collaborate across party lines. This article is primarily concerned with how institutional arrangements—specifically term limits—structure legislators' decisions to cosponsor bills with partisan opponents. Using data on bill cosponsorship from 41 states (82 chambers), we demonstrate that term limits reduce bipartisan cosponsorship even when controlling for average legislative tenure. We argue that term limits accomplish this by altering the incentives that legislators face. In addition, we demonstrate that the effect of term limits depends on the level of legislative professionalization. When professionalization is high, the negative effect of term limits on bipartisan cosponsorship is particularly pronounced.